With malice toward all? : the media and public confidence in democratic institutions - Moy, Patricia; Pfau, Michael, 1945-2009. (Westport, Conn. : Praeger, 2000)
Public opinion polls point to a continuing decline of confidence in the Presidency, court system, Congress, the news media, state government, public education, and other key institutions. Moy and Pfau examine the role of the media in the decline of the American public's confidence in democratic institutions.
Series Foreword -- Preface -- Acknowledgments -- I. Crisis of confidence -- 1. Erosion of confidence -- 2. The question of causality -- II. Media influences on confidence -- 3. Design of the studies -- 4. Media depictions of institutions -- 5. The print media's contribution -- 6. The effects of traditional television news -- 7. The effects of television programming -- 8. The effects of political talk radio -- 9. Conclusions -- References -- Index.
Includes bibliographical references (pages 191-210) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Mass media -- Political aspects -- United States; Mass media -- Public opinion; Mass media -- Influence; Public opinion -- United States; Democracy -- United States; United States -- Politics and government -- 1993-2001.; Mass media -- United States -- Influence; Médias -- Aspect politique -- États-Unis.; Médias -- Opinion publique; Médias -- États-Unis -- Influence; Démocratie -- États-Unis.; États-Unis -- Politique et gouvernement -- 1993- -- Opinion publique; Médias -- Influence; Opinion publique -- États-Unis.; États-Unis -- Politique et gouvernement -- 1993-2001.; SOCIAL SCIENCE -- Media Studies; Democracy; Mass media -- Influence; Mass media -- Political aspects; Mass media -- Public opinion; Politics and government; Public opinion; United States; Democratie; Vertrouwen; Publieke opinie; Massamedia; Communication & Mass Media; Journalism & Communications; Médias et opinion publique -- États-Unis -- 20e siècle.; Médias -- États-Unis -- Objectivité.; Médias -- Etats-Unis -- Influence; Institutions politiques -- Etats-Unis -- Opinion publique; Opinion publique -- Etats-Unis -- 1990-.; États-Unis -- Politique et gouvernement -- 20e soiècle.; Demokratie; Massenmedien; Politische Institution; Vertrauen; Öffentliche Meinung; USA; Mass media -- Political aspects -- United States; Mass media -- Public opinion; Mass media -- Influence; Public opinion -- United States; Democracy -- United States; United States -- Politics and government -- 1993-2001.; 1993-2001; Opinion shifts; Opinion manipulation; Mass media; Government agencies; Government performance; United States; Overseas item